Percepção de risco na paisagem pelos moradores do entorno da barragem do departamento nacional de obras e saneamento (DNOS), na cidade de Santa Maria RS - Silva, Rafael Silveira da (2013)
This work has the objective to analyze and interpret the perception of risk on the landscape of residents surrounding the DNOS dam, located northeast to the city limits in Santa Maria - RS. The research is part of a humanistic approach of geographic knowledge for it values the subjective aspects and life experience of the individuals as a source of knowledge. This research involved 47 subjects of both sexes, over 21 years old, living in the vicinity of the DNOS dam. The subjects were randomly invited to submit their individual perceptions of risk on the landscape in the study area, by means of an interview form, with open and closed questions, consisting of two parts. The methodology used was suggested by Whyte (1977) and also used by Sartori (2000), which consists of a methodological research triangle formed by the triad observing, asking and listening and recording. In the data analysis and tabulation, it was found that out of the 47 respondents 75% are women and 25% men, mostly aged between 21 and 60 years old or older and residence time from 6 months to 50 years. Most of them have not finished primary school and work as housewives, housemaids and/or self-employed. Regarding the perception of risk on the landscape where the residents live, it was determined that 59% of the interviewed residents recognize the risk to which they are exposed daily in the place of their residence. In the spatial area of the research, many areas of landslide risk and floods were presented causing a substantial part of the population to be highly vulnerable to floods and landslides, especially in the months of September and October, according to Sartori (2000), rainfall is more intense.